Enhancing Reading Comprehension Through Wordwall Interactive Learning In English Language Teaching - Pratiwi, Resdilla; Agustina Damanik, Lia; Rosada, Bintang (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
This study aimed to explore the effectiveness of Wordwall, an interactive learning platform, in enhancing reading comprehension skills in English language teaching. The research focused on how the platform’s interactive and gamified activities could improve students’ engagement, focus, and overall comprehension abilities. Through qualitative data collected from student interviews, teacher observations, and classroom activities, the study revealed that Wordwall significantly increased student participation and engagement compared to traditional teaching methods. The platform’s dynamic features, such as matching games and sequencing tasks, helped students better identify main ideas, infer meanings from context, and summarize information. Teachers reported that students remained more focused during lessons, with the interactive nature of the activities reducing distractions. Additionally, the study highlighted challenges such as limited internet access and the need for more varied activity types. The findings suggest that Wordwall can be a valuable tool in developing reading comprehension skills, offering a more engaging and interactive approach to English language teaching. Recommendations include addressing technical limitations and providing more diverse learning materials to enhance the platform’s effectiveness.